The Impact of Career Anchors on Job Satisfaction of Bank Managers in State Owned Commercial Banks of Sri Lanka - Wanigasekara, W.M.S.K.; Muthukumarana, P.P.S. (Faculty of Commerce and Management Studies, University of Kelaniya, 2015)
Intense customer care is one of the best practices adopted by the private sector commercial banks and this has become a critical success factor that differentiates their service from the service of state banks. Hence, employee job satisfaction is a significant matter of concern for the state banks to face this challenge and achieve service excellence. Therefore, this study investigates the impact of individuals’ selfconcept on job satisfaction in terms of career anchor concept proposed by Edgar Schein. A purposive sample of 108 managers from Bank of Ceylon and People’s Bank head office were selected by using simple random sampling technique. The independent variable representing career anchors includes the following three dimensions; talent based career anchors, need based career anchors, value based career anchors while the dependent variable job satisfaction was analyzed under two dimensions namely; intrinsic factors and extrinsic factors. There are four hypotheses were formulated using deductive approach. A self-administered questionnaire was distributed among the respondents to collect data for the research. Descriptive statistics were used to present the characteristics of the sample of the study. Furthermore the Pearson correlation coefficient and regression analysis were used to measure the impact of career anchors on job satisfaction. The study found that there is a significant impact of need based career anchors on job satisfaction whereas talent based and value based career anchors have no significant impact on job satisfaction of managerial staff at state owned commercial banks.
Keywords: Career Anchors; Job Satisfaction; State Owned Commercial Banks